Studi Kelayakan Sistem Kompresi Uap Sekali Jalan untuk Aplikasi Penyimpanan Gas Menggunakan R-32 pada Pendingin Ruangan Residensial - Anisa Ramadhani; Haolia Rahman; Fauzan; Paulus Sukusno (MBI, 2025)
R-32 presents a technically viable and environmentally sustainable option for one-shot vapor compression gas storage in residential AC, provided measures logger record and compressor innovations are prioritized. The study highlights challenges, including R-32’s elevated discharge temperatures (30°C), which necessitate advanced compressor technologies such as liquid injection to maintain reliability. Experimental data from cold storage applications demonstrate achievable evaporator temperatures of 28°C - 31°C under hybrid energy conditions, suggesting adaptability to residential AC demands.